Augusta: Rua de mão dupla - Montagnana, Laís [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
This project is about a book-report, which will discuss the Augusta Street in São Paulo, a place emblematic of the city, one of its biggest and most famous streets and that has been the scene of several transformations of the country. From the heady days of Jovem Guarda to the decadence of the inferninhos locus of prostitution and drugs. Currently the route passes through a dubious process of revitalization. Then comes the question of when life ceased to exist in Augusta and the desire to capture in words the transitory moment what is happening in this street. When you scroll through 3 km of the street you want to be seen as a flaneur, the two Augusta, one which lives on day and another whose life begins at night. Down the hills, draw a profile of one extraordinary street and lay bare the contradictions that make Augusta a two-way street

O presente trabalho consiste num livro-reportagem que aborda a Rua Augusta de São Paulo, um local emblemático da cidade, uma de suas ruas mais importantes e famosas e que já foi cenário de várias transformações do país. Dos áureos tempos da Jovem Guarda à decadência dos inferninhos lócus de prostituição e drogas. Atualmente a via passa por um processo de duvidosa “revitalização”. Surge então o questionamento de quando parou de existir vida na Augusta e a vontade de captar através de palavras esse momento transitório que está acontecendo no logradouro. Ao percorrer os 3 km da rua pretende-se observar, como um flâneur, as duas Augustas, aquela que vive durante o dia e a outra cuja vida começa à noite. Ao descer as ladeiras, traçar um perfil da rua única e extraordinária e desnudar as contradições que fazem da Augusta uma via de mão dupla
Keywords: Jornalismo - Aspectos politicos; Cidades e vilas - Melhoramentos publicos; Planejamento urbano - História; Journalism - Political aspects; São Paulo, Região Metropolitana de (SP)